Peran Persepsi Manajemen CSR dalam Memoderasi Dampak Paparan Pencemaran Terhadap Tingkat Keluhan Kesehatan Masyarakat Sekitar di PT. Bumi Mineral Sulawesi - Nur Fadhilah Safrillah; Abri Hadi; Yayuk Pratiwi Seran (Journal of Digital Literacy and Volunteering, 2026)
Indonesia's nickel smelting sector has undergone accelerative expansion yet generates substantial health implications for populations surrounding operational sites. This investigation explores the function of managerial cognitive constructions regarding corporate social accountability in moderating correlations between contaminant exposure and manifestations of community health grievances at PT Bumi Mineral Sulawesi. Applying explanatory case study methodology with data source triangulation, the investigation involved comprehensive interviews with corporate managerial structures, affected communities, and systematic documentation analysis. Findings indicate pollutant exposure contributes to escalating respiratory dysfunction and hydrological source degradation affecting collective welfare. Managerial perceptions regarding social responsibility demonstrate moderative potential, constrained by limited implementation, reactive orientation, transparency deficiency, and community participation limitations. The study confirms the urgency for social responsibility transformation toward strategic integration responsive to health necessities through health surveillance construction, emission control technology investment, and participatory governance mechanisms to actualize equilibrium between economic expansion and sustainable social prosperity